The effect of diminished metabolic acidosis on thermoregulatory response during exercise - Mikulski, Tomasz; Górecka, Monika; Smorawiński, Jerzy; Rachwalski, Krzysztof; Kryściak, Jakub; Nazar, Krystyna; Ziemba, Andrzej (Biology of Sport, 2024)
It was reported that metabolic acidosis inhibits the activity of warm-sensitive hypothalamic neurons. The present study was designed to test the hypothesis that metabolic alkalosis may improve heat loss during intensive exercise in men. Fifteen male subjects aged 22–24 years were submitted to incremental exercise on two randomized occasions one week apart. During the bicarbonate trial exercise was preceded by ingestion of NaHCO3 at a dose 250 mg/kg whilst during the placebo trial lactose was administered. Exercise load was increased every 3 min by 30 W until volitional exhaustion. Ambient temperature was kept at 23–24°C and humidity 50–60%. Tympanic and skin temperatures were recorded and the rate of sweating was assayed by humidity measurement of nitrogen flowing through a capsule attached to the mid posterior chest. Total sweat loss was determined by the changes in body mass. Venous blood samples were taken before exercise and at the end of each workload for determination of acid-base parameters. The subjects attained similar maximal workload in the two tests (260±6 W) with heart rate 185±6 beats/min. Blood concentration of hydrogen ions was lower (p < 0.001) in the bicarbonate than in the placebo trial throughout the whole exercise period. There were no significant differences between these tests in tympanic and mean skin temperatures, sweating rate and total sweat loss. The present data showed that in men attenuation of metabolic acidosis by bicarbonate ingestion did not influence thermoregulation during incremental exercise performed until volitional exhaustion, possibly due to too short duration of exertional uncompensated metabolic acidosis.